Farmers’ And Retailers’ Knowledge Level Associated with Pesticide Distribution and Application in Horticultural Production Centers in Karo Regency, North Sumatera - Hermanto, Catur; Tarigan, Rasiska; Marpaung, Agustina E.; Hutabarat, Rina C. (Yayasan Pertanian Tropika Indonesia (YPTI), 2019)
The description of the agriculture success is inseparable from the level of knowledge of retailers and farmers on the effective use of pesticides in the field. This study aimed at evaluating the relationship between the level of knowledge of retailers and farmers on the distribution and use of pesticides in vegetable production centers in Karo Regency. The research wasÂ Berastagi Experimental Farm from August to September 2016. The research method used in the survey was a cross-sectional study approach. The selection of districts was done purposively based on the highest number of retailers, the largest horticultural planting area, and the number of vegetable farmers per district. The number of research samples was 10 respondents per district. To analyze the relationship between variables, we used Spearman's range correction coefficient calculation and validity test using SPSS correlation 17. The results exhibited that the level of knowledge of retailers and farmers in Karo regency is low about the functions, codes, and formulations of all pesticides that have been distributed. The level of knowledge of vegetable farmers on the use of pesticides in Karo district is low, seen from the high level of use, increasing concentration of pesticides and high frequency of spraying, as well as mixing fungicides and insecticides 2 types of pesticides with different codes and active ingredients. The relationship of farmers' knowledge with their age, education and the length of farming experience significantly influenced the perception and attitude of using pesticides to control pest attacks in their lands of cultivation.